The Pacific Islands an encyclopedia - Lal, Brij V.; Fortune, Kate (University of Hawai'i Press, 2000)
An encyclopaedia of information on major aspects of Pacific life, including the physical environment, peoples, history, politics, economy, society and culture. The CD-ROM contains hyperlinks between section titles and sections, a library of all the maps in the encyclopaedia, and a photo library.